Metal motiliny demonstration ware - ZHU WANJING (2016)
The utility model relates to a metal motiliny demonstration ware, its characterized in that: constitute by amplifier box (1) and reaction (2), amplifier box (1) hou bi upper portion is equipped with fluorescent lamp (3), and the antetheca lower part is equipped with a plurality of convex lens (5) side by side, reaction (2) bottom is equipped with stabilizer blade (4), and place in amplifier box (1) reaction (2), and amplifier box (1) top is equipped with test tube fixed plate (6), and test tube fixed plate (6) are equipped with a plurality of round holes side by side, and test tube (7) are passed from this round hole, and test tube (7) are located reaction (2), amplifier box (1) and reaction (2) is the transparent body. Found fair experiment condition, make the conclusion of contrast test more convincing, experiment phenomena enlargies, does benefit to all students and observes, utilize broken test tube as reactor, waste product reuse, resources are saved.